A method comparison of block based accelerometers and force sensors for determination of response times in the sprint start - Holmes, J.; Hayes, K.; Harrison, A. J. (ISBS Proceedings Archive (Michigan), 2020)
This study compares sprint start response times (RT) derived from load cells in the blocks with a RT from rail mounted accelerometer using methods similar to World Athletics (WA) approved start information systems (SIS). Seven national and international sprinters completed sprint trials that replicated race competition start procedures. Load cells were incorporated into starting blocks and the back block RT were analysed using: visual inspection (Visual RT), a 3SD threshold and CUSUM method, the rail accelerometer RT were analysed using a Visual RT and a 3SD Threshold method. On average the Rail Visual RT was detected 21 ms after the Visual Back Block RT and the Rail 3SD RT detected 27 ms after the Back Block 3SD RT. The results indicated the rail accelerometer detected RT after the back block load cells, highlighting the need for a review of SIS hardware and event detection software.